Catalytic deactivation mechanism research over Cu/SAPO-34 catalysts for NH3-SCR (I): The impact of 950 °c hydrothermal aging time. (2nd February 2018) - Fan, Dequan; Wang, Jun; Yu, Tie; Wang, Jianqiang; Hu, Xiaoqian; Shen, Meiqing
Graphical abstract: This work firstly unveiled deactivation mechanism of Cu/SAPO-34 after 950 °C aging. Highlights: 950 °C hydrothermal treatment greatly decreases NO conversion of Cu/SAPO-34. SAPO-34 support transforms into SiO2 and AlPO4 phase after 950 °C aging. Si-OH-Al bond breakage weakens acidity and declines isolated Cu 2+ . Activity decline is caused by inferior Cu 2+ reducibility and weak acidity from structure damage. Abstract: The hydrothermal stability of Cu/SAPO-34 catalysts under different treatment time (3 h, 6 h, 12 h) at 950 °C has been investigated to understand their framework collapse and deactivation mechanism for NO reduction by ammonia selective catalytic reduction (NH3 -SCR). It was seen that SCR activities declined dramatically after 12 h aging, and XRD results showed this treatment led to crystallinity decline since 3 h. Furthermore, zeolites crystal started to transform into SiO2 and AlPO4 phase since 6 h. NMR results further proved the formation of SiO2 and AlPO4 ·NH3 -TPD and ex-situ DRIFTS results revealed the breakage of Si-OH-Al bonds and the decline of the number of Brønsted acid sites, meanwhile, H2 -TPR and EPR results proved that the number of Cu 2+ species decreased and the location of Cu 2+ species changed after this treatment, which were mainly responsible for declined SCR reaction rates.